Die Rutschungen am Eichberg bei Achdorf (Wutach) - Erscheinungsformen, Mechanik, Ursache - Reichelt, Günther (ERDKUNDE, 1967)
Data for the reconstruction of the slip events and their mechanics can be obtained from mapping of form elements. From this, it can be seen that the slipping on the Eichberg in 1966 was a serial slip moving from top to bottom along curved slip faces. Discussion of causes makes clear the coincidence of many factors favourable to slipping, which in their totality are only comprehensible in terms of the special location and measure of the slipping. Steep slopes and the geological underlay of spring-generating Brown Jura Clays provided essential preconditions. To these were added thick debris mantles of marked permeability which reduced the shear resistance capacity of the potential slip zone between debris and clay. Exceptionally high precipitation in the period before the slip seeped through to act as a lubricant for the slip material. Furthermore, woodland encouraged seepage and contributed to the trigger action. The comparatively high proportion of arable land may have been effective in the same way.